De Fadas e Princesas: Afetos Femininos em Marina Colasanti - Dodô, Marlucia Nogueira do Nascimento (2010)
It investigates the representations of feminine affection in fairy tales of Colasanti Marina, considering the dialogue with the traditional narrative and pointing out it in the context of the narrative contemporary, over all of the Brazilian literature destined to the infantile public. The corpus of the research understands books of fairy tales an Uma ideia toda azul (1979), Doze reis e a moça no labirinto do vento (1982), Entre a espada e a rosa (1992) and Longe como o meu querer (1997). It approaches the profile of the feminine personages and its function in the delicate relation of affection with the opponent masculine figure, generally the father, and the faced tests to reach the maturity, materialize through the individuation, of the marriage or the emancipation in relation the forces oppressors of the masculine domain. It identifies in the narrative of the author the construction of the feminine identity and the determination incorporated for the protagonists, young in age to marry, front to the discovery of the love and the privacy